IDENTIFICATION OF NOMINAL DYNAMIC CHARACTERISTICS OF AIRCRAFT GAS TEMPERATURE SENSORS - A. F. Sabitov; I. A. Safina (Приборы и методы измерений)
The existing methods only allowed to determine the dynamic or average characteristics of specific copies of gas temperature sensors as the airflow test results of a limited number of specific copies of gas temperature sensors were carried out on a certified airflow equipment. The actual operating conditions of aircraft gas temperature sensors significantly differ from those at airflow equipment. The aim of the study was to develop methods of recalculation of a test results of a limited number of gas temperature sensors that were received at certified airflow equipment and to get nominal dynamic characteristics of a particular type of gas temperature sensors in the anticipated operating conditions.This study offers the algorithm for the identification of the nominal dynamic characteristics of gas temperature sensors that are used to measure the temperature of gases in aircraft gas turbine engines. The algorithm makes it possible to 1) register the transient characteristics of gas temperature sensors of a particular type at a predetermined rate of air flow, 2) calculate the heat transfer coefficient between the gas temperature sensors and the air flow at each airflow rate, 3) measure the average transient characteristics of the gas temperature sensors at each airflow rate, 4) set the parameters of the hyperbolic function of the nominal variables of the time constants of selected gas temperature sensors from the heat transfer coefficient. The heat transfer coefficient is calculated based on the expected operating conditions of the gas temperature sensors.The result of the study was that the parameters of the hyperbolic function of the nominal variables of the time constants for the dynamic model of the second order gas temperature sensors were found. The developed method makes it possible to predict the dynamic performance of the specific types of gas temperature sensors in the expected operating conditions.